PENGARUH PENERAPAN SLOW-STROKE BACK MASSAGE DENGAN VCO (VIRGIN COCONUT OIL) TERHADAP PENURUNAN TEKANAN DARAH DAN NYERI KEPALA PADA LANSIA PENDERITA HIPERTENSI DI BANJAR DUKUH KELURAHAN SERANGAN - Rini Puspa Dewi; Putu Wira Kusuma Putra; Anak Agung Ngurah Nara Kusuma (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
Headache is a problem that is often felt by patients with hypertension. One of the non-pharmacological therapies that can reduce hypertension and pain is SSBM (Slow Stroke Back Massage) with VCO (Virgin Coconut Oil). This massage can relieve muscle tension, relax the patient and improve circulation. The purpose of this study was to determine the effect of cutaneous stimulation application: slow stroke back massage with VCO (Virgin Coconut Oil) on decreasing blood pressure and headache in elderly patients with hypertension in Banjar Dukuh, Serangan District. The design of this study was a Quasy Experimental Design with a Non Equivalent Control Group design. The sampling technique used was purposive sampling with a sample size of 30 respondents. The research instrument used an observation sheet, VAS (Visual Analogue Scale), SOP (Standard Operating Procedure) and a demographic data questionnaire. The statistical test used was the Wilcoxon Signed Rank Test and the Mann Whitney U Test with the Shapiro Wilk normality test. The results of the Wilcoxon Signed Rank Test showed a probability value of blood pressure (sig) 0.001 (p <0.05) and a probability value of headache (sig) 0.001 (p <0.05). The results of the Mann Whitney U Test obtained a probability value of blood pressure (sig) 0.001 (p <0.05) and a probability value of headache (sig) 0.002 (p <0.05). In conclusion, Ha was accepted, which means that there was an effect of cutaneous stimulation application: slow stroke back massage with VCO (Virgin Coconut Oil) on decreasing blood pressure and headache in elderly patients with hypertension in Banjar Dukuh, Serangan District. Based on the results of this study, it is expected that SSBM therapy with VCO can help to reduce blood pressure and headaches, especially in elderly people with hypertension who choose non-pharmacological treatment.